University Music Educators Creating Piano-Learning Environments in Finnish Primary School Teacher Education - Sepp, Anu; Hietanen, Suvi Lenita; Enbuska, Simo Jukka Tapani; Tuisku, Vesa Tuomas; Ruokonen, Inkeri; Ruismäki, Heikki (The European Journal of Social & Behavioural Sciences, 2019)
The importance of supportive learning environments has been considered of utmost importance. In Finnish universities where the educational entities are being re-organised, teacher educators have to reconsider and also reorganise the learning environments to sustain the quality of teaching. At the Universities of Helsinki and Lapland, where the primary school student teachers' music programmes are under serious pressure, a large scale research project “Arctic Reformative and Exploratory Teaching Profession” (ArkTop), was launched, aiming to support teachers’ life-long professional development by organizing research based in-service courses, thus, providing possibilities for cooperation and creating networks between universities and comprehensive schools in Lapland through shared expertise, critical reflections and research. Part of this project focuses on different possibilities for developing music, including piano courses in primary school teacher education. In this particular study, the issues of piano-learning environments are examined. The study focuses on mapping the main problems and finding possible solutions in music programmes for creating supportive piano-learning environments in primary school teacher education by analysing topic-specific curricular documents of both universities and the interview data drawn from a number of lecturers. In order to create the best possible learning environments, it is essential to explore how university music educators comprehend the opportunities for designing piano-learning environments.